Role of Adjuvant Radiosurgery after Thoracoscopic Microsurgical Resection of a Spinal Schwannoma. (18th July 2012) - Niazi, Toba N.; Bowers, Christian A.; Schmidt, Meic H.
Abstract : Stereotactic radiosurgery to benign tumors of the spine has not been advocated as a primary treatment modality because of the favorable prognosis for these lesions after gross-total resection. There is even less evidence regarding its use as an adjuvant to neurosurgical resection of benign recurrent spinal disease. We describe the case of a 30-year-old man with a thoracic spinal schwannoma who had an interval increase of his lesion five months after thoracoscopic microsurgical resection. The patient opted for noninvasive stereotactic radiosurgery in lieu of additional surgical excision and has had stable disease 15 months after radiosurgical treatment with the linear accelerator (LINAC) system. In this setting, stereotactic radiosurgery provided a useful adjunct to thoracoscopic microsurgical resection. Future Class I and II evidence should be sought to evaluate the utility of stereotactic radiosurgery as a primary treatment modality or as an adjuvant for microneurosurgical resection of benign spinal lesions in patients who want noninvasive treatment after disease recurrence or who harbor medical comorbidities that would preclude them from being safe surgical candidates.